Front Cover: Amino Assisted Protonation for Carbon−Carbon Coupling During Electroreduction of Carbon Dioxide to Ethylene on Copper(I) Oxide (ChemCatChem 20/2021). Issue 20 (24th September 2021) - Deng, Hongwei; Guo, Chenyan; Shi, Penghui; Zhao, Guohua
Abstract : The Front Cover shows an amino‐modified copper(I) oxide catalyst reduces the Gibbs free energy for electrocatalytic reduction of carbon dioxide to ethylene. The roller coasters and tracks represent the catalysts and the Gibbs free energy, respectively. In their Full Paper, H. Deng et al, illustrate that the modification of amino on copper(I) oxide promotes the hydrogenation of *CO to *CHO, which is the rate‐determining step for the formation of ethylene. This work presents an amino‐assisted carbon‐carbon coupling mechanism during electroreduction of carbon dioxide to multi‐carbon products. More information can be found in the Full Paper by H. Deng et al .